A scoping review on determinants of active ageing in Southeast Asian Region - Salih, Sarah; Hamid, Tengku Aizan; Ibrahim, Rahimah; Ashari, Asmidawati; Abdullah, Siti Farra; Chai, Sen Tyng (Penerbit Universiti Kebangsaan Malaysia, 2023)
Many developing countries face a rapidly ageing population requiring sufficient preparation to integrate various services for enhancing healthy active ageing. However, there is a lack of evidence on the comprehensive framework of active ageing and its overall determinants, especially in the Southeast Asia region. The current review sought to understand the main determinants of active ageing to predict the indicators of active ageing in the Southeast Asia region. A scoping review is conducted by reviewing English language literature published between 2002 and 2022 in three electronic databases, including Scopus, ScienceDirect, and PubMed, using MeSH terms, keywords, and inclusion and exclusion criteria. The review found a wide range of variables related to five determinants of healthy ageing in Southeast Asia. Participation in social, physical, learning, and labour activities is the most frequent and popular determinant of active ageing in Southeast Asia. Followed by health (health services and health status), perceived environment (neighbourhoods and housing), security (financial security, social status, and independency), behavioural (spirituality and lifestyle), and personal demographic characteristics, respectively. Overall, this scoping review contributed to the identification of comprehensive indicators of active ageing in Southeast Asia, including Malaysia.